CONTROLE DO USO ABUSIVO DO ÁLCOOL COM PSICOFÁRMACOS. - Cândido Duarte, Michell Platiny; da Fonseca Lins, Suerda Lillian; dos Santos Silva, Glauber Weder; Ferreira de Sena, Romeika Carla; Ramos Isoldi, Deyla Moura; de Castro Marcolino, Emanuella; Santos Cavalcante, Eliane; Nunes de Miranda, Francisco Arnoldo (Journal of Nursing UFPE / Revista de Enfermagem UFPE, 2018)
Objective: to identify the main positive effects of treatment with psychoactive drugs in the control of alcohol abuse. Method: this is an integrative review, without temporal delimitation, in MEDLINE, CINAHL and LILACS databases. Incorporation of evidence was used. The procedures adopted for the critical analysis of the studies in three crossings identified 77 potentially eligible publications. In the end, five of them were selected by two independent researchers, using an instrument adapted to verify the level of evidence. Results: three psychoactive drugs were identified: acamprosate presented better tolerance and did not prevent late recurrence; naltrexone does not reduce the frequency of drinking, but reduces the intensity of consumption when used alone; the disulfiram effective in abstinence, with varied reactions. Conclusion: it is concluded that the results of the treatment of alcohol abuse with psychoactive drugs present high level of evidence, conditions, and recommendations for primary and secondary outcomes.